Optimization and Modeling of Angular Deep Drawing Process for Square Cups - Ozek, Cebeli; Unal, Engin (Taylor & Francis Inc, 2011)
In this study, an attempt has been made to investigate the effects of die/blank holder angles, blank holder force, and die/punch diameter on the limit drawing ratio, punch force, and minimum wall thickness of DIN EN 10130-1999 steel sheets in angular squared deep drawing process. For this purpose, the die/blank holder profiles were machined 0 degrees, 5 degrees, 10 degrees, and 15 degrees with punch/die diameter of 8, 12, and 16 mm, respectively. A full factorial experimental design method was used for data collection. Regression analysis, signal-to-noise ratio and analysis of variance (ANOVA) were employed to the study to determine the optimal conditions and model the process. The results showed that the deep drawing ratio limits were increased at higher die/blank holder angles and die/punch diameter. The more uniform cup surfaces were observed with lower blank holder forces than standard dies.
Keywords: Angular deep drawing; Limit drawing ratio; Squared cups; Taguchi method